Fukutin mutations in non-Japanese patients with congenital muscular dystrophy: less severe mutations predominate in patients with a non-Walker-Warburg phenotype - Yiş, Uluç; Uyanik, Gökhan; Bambul Heck, Pinar; Smitka, Martin; Nobel, Hannes; Ebinger, Friedrich; Dirik, Eray; Feng, Lucy; Kurul, Semra H.; Brocke, Katja; Unalp, Aycan; Özer, Erdener; et al. (Neuromuscular disorders, 2011)
Six genes including POMT1, POMT2, POMGNT1, FKRP, Fukutin (FKTN) and LARGE encode proteins involved in the glycosylation of α-dystroglycan (α-DG). Abnormal glycosylation of α-DG is a common finding in Walker-Warburg syndrome (WWS), muscle-eye-brain disease (MEB), Fukuyama congenital muscular dystrophy (FCMD), congenital muscular dystrophy types 1C and 1D and some forms of autosomal recessive limb-girdle muscular dystrophy (LGMD2I, LGMD2K, LGMD2M), and is associated with mutations in the above genes. FCMD, caused by mutations in Fukutin (FKTN), is most frequent in Japan, but an increasing number of FKTN mutations are being reported outside of Japan. We describe four new patients with FKTN mutations and phenotypes ranging from: severe WWS in a Greek-Croatian patient, to congenital muscular dystrophy and cobblestone lissencephaly resembling MEB-FCMD in two Turkish patients, and limb-girdle muscular dystrophy and no mental retardation in a German patient. Four of the five different FKTN mutations have not been previously described.
Available online 18 October 2010
Gesehen am 12.12.2022